META-ANALISIS PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA - Novi Indah Lestari; Abdul Razak; Lufri Lufri; Zulyusri Zulyusri; Fitri Arsih (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this study was to analyze the effect of using the Teams Games Tournament (TGT) learning model on student learning outcomes. This research method is a meta-analysis by examining data sources originating from national or international journals published in the last seven years (2014-2021). This research begins with formulating the topic to be studied, then formulating the problem and research objectives, at the next stage collecting relevant articles to collect data. The data was obtained from online journal searches through Google Scholar. The keywords used are